Fundus flavimaculatus: Clinical images and review of literature (Indian Journal of Case Reports, 2018)
Stargardt disease (STGD) or fundus flavimaculatus is a progressive form of juvenile macular degeneration with considerable clinical and genetic heterogeneity. It may be considered a syndromal cone-rod dystrophy due to overlapping clinical features such as loss of color vision and photophobia in some patients. Here, we report a case of fundus flavimaculatus in a 32-year-old female and discuss the literature pertaining to it. Clinical data including medical history, findings on physical examination and local examination were suggestive of fundus flavimaculatus. Best-corrected visual acuity of the patient remained constant at 6/12 for 1 year with the patient being on 3-month follow-up. No particular or specific treatment is available for this fundus dystrophy and frequent follow-ups may help diagnose and manage associated choroidal neovascular membrane at the earliest. The only modality is available in the form of low vision aids for advanced disease.